Optimization of residual coalbed methane extraction wells and analysis of development and emission reduction benefits in the Songzao mining area - Yaxin Xiu; Qinjie Liu; Qiang Fu; Ke Yang; Miao Zhang; Benniu Wu (Scientific Reports)
Abstract The utilization of coalbed methane (CBM) resources in closed coal mines is crucial for energy transition and green low-carbon development. This study systematically analyzed geological factors, CBM reserves, and economic factors to evaluate the potential of CBM extraction from the Songzao mining area of Chongqing. An evaluation indicator system was established, comprising 3 primary indicators, 13 secondary indicators, and 5 closed coal mines as the scheme layer. This system facilitated accurate quantification of feasibility evaluation weights for CBM extraction under complex geological conditions. The game theory was employed to refine the integration of subjective and objective weights, which ensured the objectivity and accuracy of the evaluation results. A feasibility evaluation model for CBM extraction from goafs in closed coal mines was constructed using the TOPSIS method, with results ranked as follows: Songzao coal mine > Fengchun coal mine > Shihao coal mine > Yuyang coal mine > Datong No. 1 coal mine. Furthermore, the trends in energy conservation and emission reduction benefits over the past eight years since the closure of the Songzao coal mine were analyzed, encompassing both CBM emissions and power generation. The findings highlight the necessity of CBM extraction from goafs in closed coal mines in China and demonstrate the significant potential of CBM resource development for reducing greenhouse gas emissions and promoting clean energy alternatives, providing a reference for theoretical research and practice.